Fetal right ventricular contraction and relaxation times at 11–13 weeks' gestation on speckle tracking imaging. (1st January 2014) - Persico, N.; Fabietti, I.; Baffero, G. M.; Fedele, L.; Nicolaides, K. H.
ABSTRACT Objective To examine the contraction time and relaxation time of the right ventricle at 11–13 weeks' gestation in trisomy 21 and euploid fetuses by speckle tracking ultrasound imaging. Methods Measurement of fetal nuchal translucency (NT) thickness, Doppler assessment for tricuspid regurgitation and reversed A‐wave in the ductus venosus (DV) and fetal echocardiography were performed immediately before chorionic villus sampling for fetal karyotyping at 11–13 weeks' gestation. Digital videoclips of the four‐chamber view of the fetal heart were recorded and analyzed offline using speckle tracking imaging software. The contraction time, which is the time between the highest and lowest peaks in the right ventricular area, and relaxation time, which is the time between the lowest and the subsequent highest area peak, were measured and expressed as a percentage of the duration of the cardiac cycle. Values in trisomy 21 and euploid fetuses were compared. Results Mean contraction time and relaxation time in 119 euploid fetuses were 52.1% (95% CI, 51.6–52.8%) and 47.8% (95% CI, 47.2–48.4%), respectively. In 21 trisomy 21 fetuses, mean contraction time was significantly higher (57.0% (95% CI, 55.2–58.9%); P < 0.01) and relaxation time lower (42.9% (95% CI, 41.1–44.8%); P < 0.01) than in euploid fetuses. Multiple regression analysis showed that significant contributions to contraction time and relaxation time were provided by fetal karyotype, NT and tricuspid regurgitation, but not by reversed A‐wave in the DV or the presence of a cardiac defect. Conclusion In first‐trimester fetuses with trisomy 21 and in euploid fetuses with increased NT and tricuspid regurgitation there is evidence of increased right ventricular contraction time and shortening of the relaxation time. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd